Printability studies of Ti-6Al-4V by metal fused filament fabrication (MF3). (September 2020) - Singh, Paramjot; Balla, Vamsi K.; Tofangchi, Alireza; Atre, Sundar V.; Kate, Kunal H.
Abstract: Predicting the influence of material composition on the printability of highly filled metal powder-polymer systems present a significant challenge in metal fused filament fabrication (MF 3 ). The current work presents an approach to evaluate new material compositions used to fabricate filaments for their printability. In this study, filaments with 59 vol.% (87 wt.%) of Ti-6Al-4V powder with two particle size distributions fine (D50 = 13 μm) and coarse (D50 = 30 μm) dispersed in a polymer matrix were examined. The respective forces to overcome the pressure drop, for successful printing, were found to increase with an increase in the feed rate, and were also dependent on the feedstock viscosity. In addition, shear forces estimated from the filament shear strength were found to be limiting conditions for successful printing. Based on these observations, a criterion has been proposed to evaluate filament printability from the predicted limiting force for filament failure and the required force to achieve continuous material flow for successful printing. Under present experimental conditions, successful printing was achieved up to 2 mm/s and 8 mm/s for fine and coarse powder filaments, in good agreement with the model predictions. The model was experimentally tested and found to be applicable for other compositions. The results demonstrate a new printability criterion to design novel materials for MF 3 . Highlights: Printability of Ti64 alloy powder-polymer filaments for fused filament fabrication. Filament viscosity and feed rate influences the pressure drop at the nozzle exit. Filament strength dictates successful material extrusion and printing. Powder attributes influences printability and print speed. Predictive process models allow materials development in fused filament fabrication.